Journal of Ethnobiology and Ethnomedicine - Pieroni, Andrea
Journal of Ethnobiology and Ethnomedicine publishes original research focusing on cultural perceptions of nature and of human and animal health. Journal of Ethnobiology and Ethnomedicine invites research articles, reviews and commentaries concerning the investigations of the inextricable links between human societies and nature, food, and health. Specifically, the journal covers the following topics: ethnobotany, ethnomycology, ethnozoology, ethnoecology (including ethnopedology), ethnogastronomy, ethnomedicine, ethnoveterinary, as well as all related areas in environmental, nutritional, and medical anthropology. Research focusing on the implications that the inclusion of humanistic, cultural, and social dimensions have in understanding the biological word is also welcome, as well as its potential projections in public health-centred, nutritional, and environmental policies.